Coupled Radio and X-Ray Emission and Evidence for Discrete Ejecta in the Jets of SS 433 - Miller-Jones, James; Migliari, S.; Fender, R.; Thompson, T.; van der Klis, M.; Mendez, M. (Institute of Physics Publishing, Inc., 2008)
We present five epochs of simultaneous radio (VLA) and X-ray (Chandra) observations of SS 433 to study the relation between the radio and X-ray emission in the arcsecond-scale jets of the source. We detected X-ray emission from the extended jets in only one of the five epochs of observation, indicating that the X-ray reheating mechanism is transient. The reheating does not correlate with the total flux in the core or in the extended radio jets. However, the radio emission in the X-ray reheating regions is enhanced when X-ray emission is present. Deep images of the jets in linear polarization show that outside of the core, the magnetic field in the jets is aligned parallel to the local velocity vector, strengthening the case for the jets to be composed of discrete bullets rather than being continuous flux tubes. We also observed anomalous regions of polarized emission well away from the kinematic trace, confirming the large-scale anisotropy of the magnetic field in the ambient medium surrounding the jets.